Crowns In Conflict : The Triumph and the Tragedy of European Monarchy 1910 - 1918 - ARONSON, Theo (Salem House Publishers, 1986)
Here, Theo Aronson has assembled the entire cast of embattled monarchs. His is the story of eight momentous years viewed, as it were, from the monarchical standpoint; an account of the passing, not only of their particular world, but of the entire monarchic and dynastic order of the Continent. It describes the brilliant sunset and the dramatic break-up of the Europe of the Kings.